Limit the mixed recurrence

Calculus Level 4

Let a 0 = 1 , b 0 = 2 , a_0 = 1, b_0 = 2, and for n 0 n\geq 0 a n + 1 = a n + b n 2 , b n + 1 = a n + 1 b n . a_{n+1} = \frac{a_n + b_n}{2},\quad b_{n+1} = \sqrt{a_{n+1}b_n}. If lim n a n b n = c π d \displaystyle \lim_{n\to\infty } a_n b_n = \dfrac c{\pi^ d} for positive integers c c and d d , find c + d c+d .


The answer is 29.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Mar 21, 2017

Suppose that a 0 = 2 cos x a_0 =2\cos x and b 0 = 2 b_0 = 2 for some 0 < x < 1 2 π 0 < x < \tfrac12\pi . It is a simple induction to show that b n = 2 j = 1 n cos ( x 2 j ) a n = b n cos ( x 2 n ) n 1 . b_n \; = \; 2\prod_{j=1}^n\cos\big(\tfrac{x}{2^j}\big) \hspace{1cm} a_n \; = \; b_n \cos\big(\tfrac{x}{2^n}\big) \hspace{2cm} n \ge 1 \;. and a second induction shows that b n = 2 sin x 2 n sin x 2 n n 1 b_n \; = \; \frac{2\sin x}{2^n \sin \frac{x}{2^n}} \hspace{2cm} n \ge 1 From this last formula it is clear that β = lim n b n = 2 sin x x \beta \;=\; \lim_{n \to \infty} b_n \; = \; \frac{2\sin x}{x} and therefore that α = lim n a n = lim n b n cos ( x 2 n ) = β \alpha \; = \; \lim_{n \to \infty} a_n \; = \; \lim_{n \to \infty} b_n \cos\big(\tfrac{x}{2^n}\big) \; = \; \beta In our case, x = 1 3 π x = \tfrac13\pi , and hence α = β = 3 3 π \alpha = \beta = \frac{3\sqrt{3}}{\pi} , making the answer 27 + 2 = 29 27 + 2= \boxed{29} .

How do you know working out with. Cosine function would help ? I mean a 0 a_{0} could be any function, so how cos x comes to mind ?

Vishal Yadav - 4 years, 2 months ago

You just nailed every bit of it👏👏👏

Divyansh Joshi - 4 years, 1 month ago
Kartik Sharma
Mar 21, 2017

b n + 1 2 b n = a n + 1 \displaystyle \frac{b_{n+1}^2}{b_n} = a_{n+1}

2 b n + 1 2 b n = a n + b n \displaystyle \frac{2b_{n+1}^2}{b_n} = a_n + b_n

2 b n + 1 2 b n = b n 2 b n 1 + b n \displaystyle \frac{2b_{n+1}^2}{b_n} = \frac{b_n^2}{b_{n-1}} + b_n

Dividing by b n b_n ,

2 b n + 1 2 b n 2 = b n b n 1 + 1 \displaystyle \frac{2 b_{n+1}^2}{b_n^2} = \frac{b_n}{b_{n-1}} + 1

Substitute t n = b n b n 1 t_n = \frac{b_n}{b_{n-1}} ,

2 t n + 1 2 1 = t n \displaystyle 2t_{n+1}^2 - 1 = t_n

This hints 2 cos 2 ( x ) 1 = cos ( 2 x ) 2 \cos^2(x) - 1 = \cos(2x) , so here we go,

t n = cos ( x 2 n 1 ) \displaystyle t_n = \cos\left(\frac{x}{2^{n-1}}\right)

where x = cos 1 ( t 1 ) = cos 1 ( b 1 b 0 ) = cos 1 ( a + b 2 b ) x = \cos^{-1}(t_1) = \cos^{-1}\left(\frac{b_1}{b_0}\right) = \cos^{-1}\left(\sqrt{\frac{a+b}{2b}}\right) .

b n b 0 = t n t n 1 t n 2 t 1 = k = 1 n cos ( x 2 k 1 ) \displaystyle \frac{b_n}{b_0} = t_n t_{n-1} t_{n-2} \cdots t_1 = \prod_{k=1}^n{\cos\left(\frac{x}{2^{k-1}}\right)}

The product can be found by multiplying and dividing by sin ( x 2 n 1 ) \sin\left(\frac{x}{2^{n-1}}\right) .

b n = b sin ( 2 x ) 2 n sin ( x 2 n 1 ) \displaystyle b_n = b \frac{\sin\left(2x\right)}{2^n\sin\left(\frac{x}{2^{n-1}}\right)}

β = b sin ( 2 x ) 2 x lim n 1 sin ( x 2 n 1 ) x 2 n 1 \displaystyle \beta = \frac{b\sin(2x)}{2x} \lim_{n\rightarrow\infty} \frac{1}{\frac{\sin\left(\frac{x}{2^{n-1}}\right)}{\frac{x}{2^{n-1}}}}

β = b sin ( x ) cos ( x ) x = b a + b 2 b a b 2 b cos 1 ( a + b 2 b ) \displaystyle \beta = \frac{b\sin(x)\cos(x)}{x} = \frac{b \sqrt{\frac{a+b}{2b}} \sqrt{\frac{a-b}{2b}}}{\cos^{-1}\left(\sqrt{\frac{a+b}{2b}}\right)}

Now using 2 cos 1 ( x ) = cos 1 ( 2 x 2 1 ) 2\cos^{-1}(x) = \cos^{-1}(2x^2 -1) ,

β = b 2 a 2 cos 1 ( a b ) \displaystyle \beta = \frac{\sqrt{b^2 - a^2}}{\cos^{-1}\left(\frac{a}{b}\right)}

It can be shown easily that α = β \alpha = \beta .

It has some good history. Shwaub -Shoenberg mean. Shwaub proved it by some rather geometrical rigor. Shoenberg's proof was a very different kind. He proved that b n 2 a n 2 cos 1 ( a n b n ) \frac{\sqrt{b_n^2 - a_n^2}}{\cos^{-1}\left(\frac{a_n}{b_n}\right)} is constant.

In fact a similar kind also prompted 14-year old Gauss, it was -

a n = a n + b n 2 , b n = a n b n a_{n} = \frac{a_n + b_n}{2}, b_{n} = \sqrt{a_{n}b_n}

a 0 = a , b 0 = b a_0 = a, b_0 = b .

Can anyone give me a hint how to do it?

Kartik Sharma - 4 years, 2 months ago

Log in to reply

@Mark Hennings A t n t_n can be found just like I did above but no further success.

Kartik Sharma - 4 years, 2 months ago

If a > b > 0 a > b > 0 , define a 0 = a a_0 = a , b 0 = b b_0 = b and, inductively, a n + 1 = 1 2 ( a n + b n ) , b n + 1 = a n b n a_{n+1} \; = \; \tfrac12(a_n + b_n) \hspace{0.5cm},\hspace{0.5cm} b_{n+1} \; = \; \sqrt{a_nb_n} If 0 < b n < a n 0 < b_n < a_n then it follows that 0 < b n < b n + 1 < a n + 1 < a n 0 < b_n < b_{n+1} < a_{n+1} < a_n and moreover 0 < a n + 1 b n + 1 < 1 2 ( a n b n ) 0 < a_{n+1} - b_{n+1} < \tfrac12(a_n - b_n) Thus the sequence ( a n ) (a_n) is decreasing and bounded below, and the sequence ( b n ) (b_n) is increasing and bounded above. Thus both sequences converge. Since 0 < a n b n < 2 n ( a b ) 0 < a_n - b_n < 2^{-n}(a-b) , both sequences converge to the same limit M ( a , b ) M(a,b) , called the arithmetic-geometric mean of a a and b b .


Now define I ( a , b ) = 0 d x ( x 2 + a 2 ) ( x 2 + b 2 ) I(a,b) \; = \; \int_0^\infty \frac{dx}{\sqrt{(x^2+a^2)(x^2+b^2)}} for any 0 < b < a 0 < b < a . Note that π 2 a = 0 d x x 2 + a 2 I ( a , b ) 0 d x x 2 + b 2 = π 2 b \frac{\pi}{2a} \; = \; \int_0^\infty \frac{dx}{x^2 + a^2} \; \le \; I(a,b) \; \le \; \int_0^\infty \frac{dx}{x^2 + b^2} \; = \; \frac{\pi}{2b} This integral can be expressed in term of the complete elliptic integral of the first kind.

If 0 < b < a 0 < b < a and we define a ^ = 1 2 ( a + b ) \hat{a} = \tfrac12(a+b) , b ^ = a b \hat{b} = \sqrt{ab} , then the substitution 2 x = t a b t 2x = t - \tfrac{ab}{t} gives I ( a ^ , b ^ ) = 0 d x ( x 2 + a ^ 2 ) ( x 2 + b ^ 2 ) = 1 2 d x ( x 2 + a ^ 2 ) ( x 2 + b ^ 2 ) = 0 d t ( t 2 + a 2 ) ( t 2 + b 2 ) = I ( a , b ) \begin{aligned} I(\hat{a},\hat{b}) & = \int_0^\infty \frac{dx}{\sqrt{(x^2+\hat{a}^2)(x^2+\hat{b}^2)}} \; = \; \tfrac12\int_{-\infty}^\infty \frac{dx}{\sqrt{(x^2+\hat{a}^2)(x^2+\hat{b}^2)}} \\ & = \int_0^\infty \frac{dt}{\sqrt{(t^2+a^2)(t^2+b^2)}} \; = \; I(a,b) \end{aligned}


Putting this all together, we have π 2 a n I ( a n , b n ) = I ( a , b ) π 2 b n n 1 \frac{\pi}{2 a_n} \; \le \; I(a_n,b_n) \; = \; I(a,b) \; \le \; \frac{\pi}{2b_n} \hspace{1cm} n \ge 1 and so, letting n n \to \infty , π 2 M ( a , b ) I ( a , b ) π 2 M ( a , b ) \frac{\pi}{2M(a,b)} \; \le \; I(a,b) \; \le \; \frac{\pi}{2M(a,b)} so that M ( a , b ) = π 2 I ( a , b ) M(a,b) \; = \; \frac{\pi}{2I(a,b)}

Mark Hennings - 4 years, 2 months ago

Log in to reply

Well, I appreciate what you did but does this come out of experience -

"Now define I ( a , b ) = I(a,b) = \cdots " ?

I find it difficult to follow.

Kartik Sharma - 4 years, 2 months ago

Log in to reply

@Kartik Sharma Experience, or knowing Gauss' result. The tricky part is chasing the change of variable through to show that I I does not change after one stage of AM/GM calculation. The formula for I I is readily available (Wikipedia, Mathworld), the proof is less easy to find.

Mark Hennings - 4 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...